EXPLORING STUDENTS REPORT TEXT AT THE ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Dian Rauda T. Adam; Naniek Jusnita; Sutaryo Sutaryo (Cakrawala Bahasa, 2022)
This study aims to find out how to explore the text of student reports at the Khairun University English Education Study Program. The purpose of this study was to obtain information about the text of the Exploring student report. It is a qualitative method design and uses tests to collect data. Involving 20 fifth semester students. The researcher found that the aspects written by 20 respondents were more dominant in the generic structure. Writing report text is more accurate on generic structure and more wrong in writing text on linguistic features which include grammar, and vocabulary.